LC-MS profiling highlights hazelnut (Nocciola di Giffoni PGI) shells as a byproduct rich in antioxidant phenolics. (November 2017) - Masullo, Milena; Cerulli, Antonietta; Mari, Angela; de Souza Santos, Carla Clisiane; Pizza, Cosimo; Piacente, Sonia
Abstract: The Italian "Nocciola di Giffoni", also known as "Tonda di Giffoni", a labelled Protected Geographical Indication (PGI) product, represents an important economic resource for the Italian market. The methanol (MeOH) extract of "Tonda di Giffoni" shells has been investigated for the phenolic content, assayed by the Folin-Ciocalteu method, and for the antioxidant activity by the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and Trolox Equivalent Antioxidant Capacity (TEAC) assays. In order to achieve deeper insight into the chemical composition of the shells of hazelnut "Nocciola di Giffoni" and to highlight the occurrence of biologically active compounds, a phytochemical investigation was carried out. An initial Liquid Chromatography - Mass Spectrometry (LC-MS) profile of the methanol (MeOH) extract of the shells of C. avellana, cultivar "Tonda di Giffoni" led to the identification of sixteen compounds, of which the structures were elucidated by Nuclear Magnetic Resonance (NMR) spectroscopy. These were identified as a new diarylheptanoid, giffonin V (13 ), along with fifteen known phenolic compounds belonging to diarylheptanoid, neolignan, phenilpropanoid and flavonoid classes. In order to perform the quantitative determination of the main compounds of MeOH extract of C. avellana L. shells, an analytical method based on liquid chromatography coupled to mass spectrometry (LC-MS) with electrospray ionization source (ESI) and triple quadrupole mass analyzer (QqQ), using multiple reaction monitoring (MRM) scan mode, was developed and validated. The quantitative results highlight that main compounds occurred in the extract in concentration ranging from 6.4 to 83.3 (mg/100 g). The antioxidant activity of all the isolated compounds evaluated by TEAC assay showed as the flavonoid derivatives exhibited a higher free-radical-scavenging activity. Moreover, the cytotoxicity of each compound was tested against the cancer cell lines A549 and Hela and against the human skin fibroblasts HaCat. None of tested compounds, in a range of concentrations between 12.5 and 100 μM, cause a significant reduction of the cell number. Graphical abstract: Highlights: LC-MS profile guided the phytochemical investigation of the MeOH extract of hazelnut (Nocciola di Giffoni PGI) shells. One new diarylheptanoid along with fifteen known phenolic compounds was identified. Quantitative determination of the main compounds (ranging from 6.4 to 83.3 mg/100 g) was performed by LC-ESI(QqQ)MS. Among the phenolics, the flavonoid derivatives exhibited the highest free-radical-scavenging activity, tested by TEAC assay. None of tested compounds showed cytotoxicity against A549, Hela and HaCat cell lines.